Is role playing in Requirements Engineering Education increasing learning outcome? - Svensson, Richard Berntsson; Regnell, Björn (Requirements engineering, 2017)
Requirements Engineering has attracted a great deal of attention from researchers and practitioners in recent years. This increasing interest requires academia to provide students with a solid foundation in the subject matter. In Requirements Engineering Education (REE), it is important to cover three fundamental topics: traditional analysis and modeling skills, interviewing skills for requirements elicitation, and writing skills for specifying requirements. REE papers report about using role playing as a pedagogical tool; however, there is a surprising lack of empirical evidence on its utility. In this paper we investigate whether a higher grade in a role playing project have an effect on students’ score in an individual written exam in a Requirements Engineering course. Data are collected from 412 students between the years of 2007 and 2014 at Lund University and Chalmers | University of Gothenburg. The results show that students who received a higher grade in the role playing project scored statistically significant higher in the written exam compared to the students with a lower role playing project grade.